Insertion semantics of quantum interactions - Tarasich, Yu.G.; Soloshenko, H.A. (PROBLEMS IN PROGRAMMING, 2023)
The rapid development of the chemical industry and science and new challenges in the field of health care put forward increased demands for the development of the theory of organic and inorganic chemistry, biochemistry and biophysics, the search and implementation of new modelling and analysis methods, and the improvement of technological processes.One of the safe and fast methods of researching the properties and behavior of new materials and tools is the modelling of relevant experiments, in particular, computer molecular modelling based on mathematical models.Modelling the interactions between micro and macromolecules at the quantum level allows us to manipulate the substances’ electronic, magnetic, optical and other characteristics and consider the possibilities of creating new chemical bonds, molecular structures, phase transitions, quantum states, and so on.Accordingly, the main idea of our research is to apply the technology of algebraic modelling and quantum-chemical apparatus for the simulation and verification of experiments in physics, chemistry, and biology areas.The use of formal algebraic methods allows proving properties and finding relevant scenarios for the effective analysis of the behavior of various objects in real-time, considering not individual scenarios but sets of possible behaviors.At this research stage, we have developed a methodology for formalization complex organic and inorganic substances, chemical processes and reactions based on the formalization of the interaction of atoms and molecules at the level of quantum interactions.Prombles in programming 2023; 4: 65-75